Downstream consequences of diagnostic error in pediatric anaphylaxis - H. Thomson; R. Seith; S. Craig (BMC, 2018)
Abstract Background Pediatric anaphylaxis is commonly misdiagnosed in the Emergency Department (ED). We aimed to determine the impact of inaccurate diagnosis on the management and follow-up of pediatric anaphylaxis presenting to the ED. Methods Retrospective chart review of ED management of children aged 0-18 years with allergic presentations to three EDs in Melbourne, Australia in 2014. Cases were included if an ED diagnosis of anaphylaxis was recorded, or the presentation met international consensus criteria for anaphylaxis. Results Of the 60,143 pediatric ED presentations during the study period, 1551 allergy-related presentations were identified and reviewed. 187 met consensus criteria for anaphylaxis, and another 24 were diagnosed with anaphylaxis without meeting criteria. Of the 211 presentations, 105 cases were given an ED diagnosis of anaphylaxis and 106 cases were given an alternative diagnosis in ED. Those diagnosed with anaphylaxis were more likely to receive epinephrine [85.7% vs 31.1% (OR = 13.27, 95% CI: 6.09-26.3)], to be observed for the recommended four hours [56.2% vs 29.2% (OR = 3.10, 95% CI 1.76-5.48, p < 0.001)], to have an epinephrine autoinjector available on discharge [81.9% vs 35.8% (OR = 4.12, 95% CI 2.07-8.22, p < 0.001)] and to be referred to an allergist [35.2% vs 16.0% (OR = 2.85, 95% CI 1.48-5.49, p < 0.01)]. Provision of anaphylaxis action plans and allergen avoidance advice was poorly documented for all patients. Conclusion Accurate diagnosis of anaphylaxis in ED has a significant impact on observation times, prescription of epinephrine autoinjectors and referral to an allergist. These factors are key to reducing mortality and the significant morbidity that results from childhood anaphylaxis.